O papel da instrução na produção oral de aprendizes de língua inglesa: um estudo sobre marcadores conversacionais - Gilmar Bueno Santos (2006)
This work was meant to identify and analyze the use of Discourse Markers (DMs) by EFL students, focusing on the role of formal instruction. The theoretical basis used as the criteria for determining DMs functions in the present research are studies such as Marcuschi (1986), Chiaretti (1993), Galembeck & Carvalho (1998a, 1998b), Penhavel (2005) and Jorge (1997). The analyzed data were also treated statistically in order to determine the most significant conditioning factors for the production of the phenomenon under research. The statistics program used in this research was Goldvarb 2001 (Robinson, Lawrence e Tagliamonte, 2001). The results show that the formal instruction as an element to consider in second language learning and teaching can make a contribution to the use of DMs.